2022
DOI: 10.2147/ijgm.s352511
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance and Therapeutic Target of CXC Chemokines in the Microenvironment of Lung Adenocarcinoma

Abstract: Background: Lung adenocarcinoma (LUAD) is one of the most important subtypes of lung cancer and has a high morbidity and mortality. Inflammatory CXC chemokines in tumor microenvironment can stimulate tumor growth, invasion, and metastasis, affecting the prognosis of patients. However, the differential expression profiles, prognostic values, and specific mechanisms of the CXC chemokine family in LUAD have not been clarified. Methods: Transcriptome expression profile data were extracted from TIMER and TCGA. GEPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…MIP-1α, MIP-1β and MIP-2, as important chemokines, play pivotal role in attracting immune cells to tumor tissues sites [ 22 , 23 ]. However, other studies also found that higher expression of MIP-1α, MIP-1β or MIP-2 were also associated with poorer prognosis and decreased survival rate in lung adenocarcinoma patients [ [24] , [25] , [26] ]. High levels of MIP-1α have also been linked to promoting cancer cells growth and survival by stimulating tumor neovascularization [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…MIP-1α, MIP-1β and MIP-2, as important chemokines, play pivotal role in attracting immune cells to tumor tissues sites [ 22 , 23 ]. However, other studies also found that higher expression of MIP-1α, MIP-1β or MIP-2 were also associated with poorer prognosis and decreased survival rate in lung adenocarcinoma patients [ [24] , [25] , [26] ]. High levels of MIP-1α have also been linked to promoting cancer cells growth and survival by stimulating tumor neovascularization [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, seven genes were identified as prognostic genes related to the phenotype of necroptosis, and FAM83A was one of them. In addition, these six genes (HMMR ( Li et al, 2020b ; Li et al, 2021 ), ANLN ( Zhang et al, 2020 ; Deng et al, 2021 ), RHOV ( Wang et al, 2021b ; Zhang et al, 2021 ), CXCL17 ( Liu et al, 2020 ; Wang et al, 2022 ), MS4A1 ( Ma et al, 2020 ; Song et al, 2020 ), and CCR2 ( Liu and Wu, 2021 ; Wan et al, 2021 )) have also been studied to support their use as potential prognostic biomarkers and possible immunotherapeutic targets related to LUAD, but our research supports their involvement in the incidence and development of LUAD from the perspective of cell necroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic markers and the indications for prognosis in these studies are summarized in Table 2 . 36 , 44 , 45 , 47 49 , 55 89 DEGs and their combined prognostic model were the most common types of prognostic markers in these studies. For example, one study identified nine cancer-specific DEGs (CBFA2T3, CR2, SEL1L3, TM6SF1, TSPAN32, ITGA6, MAPK11, RASA3, and TLR6) and established a prognostic risk model in combination with clinical factors.…”
Section: The Prognostic Time Markers For Luadmentioning
confidence: 91%
“…Immune cell infiltration, specifically B-cell infiltration was significantly correlated with LUAD microenvironment mediated by cysteine(C)-non cysteine(X)-cysteine(C) (CXC) chemokines. 68 In addition, Arf-GAP with coiled-coil ankyrin (ANK) repeat and PH domain-containing protein 1 (ACAP1) expression appeared to be positively associated with the infiltrating level of immune cells in TIME and the expression of immune checkpoint molecules. 76 ACAP1 was highly correlated with T-cell activation and immune response.…”
Section: The Prognostic Time Markers For Luadmentioning
confidence: 99%